Fecundity and Longevity of Spodoptera frugiperda (Lepidoptera: Noctuidae) at Constant Temperatures and Development of an Oviposition Model. Issue 6 (25th September 2022) - Heo, Jin Woo; Kim, Su Bin; Kim, Dong-Soon
Abstract: Fall armyworm, Spodoptera frugiperda (J.E. Smith), is a notorious invasive pest native to subtropical and tropical regions in the Western Hemisphere. It has recently invaded and established in south Asian countries and in South Korea only seasonally. Longevity, survival, and fecundity of fall armyworm were examined at different temperatures (16, 20, 24, 28, and 32°C) and an oviposition model was developed. The maximum observed fecundity was 1, 485 eggs per female at 22.0°C, which decreased to ca. 815 eggs at 32.0°C. Female longevity decreased as the temperature increased up to 24°C, and then was constant around 13–14 d until temperature reached 32°C, ranging from 33.1 d at 16.0°C to 13.1 d at 32.0°C. Temperature-dependent total fecundity (TDF) was well described by the extreme value function. Age-specific cumulative oviposition rate (AOR) and age-specific survival rate (ASR) curves were fitted to logistic and sigmoid functions, respectively. The model of female adults' aging rate (1/mean longevity) as a function of temperature was used to calculate the physiological age of fall armyworm females in AOR and ASR models. Three temperature-dependent components of TDF, AOR, and ASR were incorporated to construct the oviposition model, and it was simulated to project corn damage with tentative parameters. When 10 fall armyworm females were assumed, a total of 68–74 corn ears with kernel damage were predicted. Such loss was estimated to be US$75–83 currently in the Korean market. Graphical Abstract: